When Tubal Tells The Merchant of Venice as Jessica’s Story: Clive Sinclair’s “Shylock Must Die” - Anténe, Petr (American & British Studies Annual, 2021)
Shakespeare’s plays have attracted numerous reinterpretations not only on the stage, but also in other genres. Recent retellings of The Merchant of Venice by British Jewish authors, such as Arnold Wesker’s play The Merchant (1976) or Howard Jacobson’s novel Shylock Is My Name (2016), focus on a complex portrayal of Shylock as the main Jewish character. However, Clive Sinclair’s short story “Shylock Must Die” (2014) adopts a different strategy by foregrounding two other Jewish characters, as Shylock’s daughter Jessica is described from the point of view of the moneylender Tubal. In Sinclair’s version, Tubal is refashioned as a private detective who, despite his experience, can hardly believe how cunning Jessica turns out to be, as she tricks him into participating in her own scheme. While Shakespeare’s play assigns a significant amount of agency to Portia, Sinclair’s short story takes liberty in shifting the focus to another female character. As the story reports events that followed Jessica’s wedding, it may even be considered a sequel to The Merchant of Venice, and the story’s title itself suggests it has even less to do with comedy than the original. For all these reasons, “Shylock Must Die” presents a radical rewriting of Shakespeare’s text.